An Approach to Annual Reports By Agricultural Research Departments - K. Robert Kern (Journal of Applied Communications, 1992)
Leaders in agricultural research institutions in many developing countries want to publish English-language annual reports. They have few editorial and financial resources. Few have ( 1) analyzed their reasons for reporting, (2) set priorities among audiences, or (3) considered a design that would serve the audience(s). This paper proposes three main audiences for such reports: heads of agencies that use agricultural research findings, agricultural scientists, and some persons interested in agricultural science (but not scientists). An audience-friendly approach is suggested for the design and preparation of annual reports that can be more useful than those written in the usual scientific-report form.